The Relationship Between EHS and the REACH Regulation in Practice - Salagvárdi, Noémi (International Journal of Engineering and Management Sciences, 2018)
The European Union has enacted strict safety regulations on the usage of chemical substances. Not long ago the Hungarian Government has also enacted the 1907/2006/EK (REACH) regulation and 1272/2008/EK (CLP) regulation. With the acceptance of the decrees our knowledge and available information about chemicals has expanded, due to the reporting obligation. As a consequence the usage of hazardous chemical compounds will be safer for the people and the environment. With the access to the shared data, we will be able to make appropriate decisions despite lacking previous measurements of our own. My goal is to present the hazardous information profiles form the packages of the REACH and CLP, and their possible applications.